1983
DOI: 10.1021/ma00241a018
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of ionizable polymers on ionic surfaces: poly(acrylic acid)

Abstract: The adsorption behavior of ionized poly(acrylic acid) on tribasic calcium phosphate surfaces from aqueous solutions has been studied by Fourier transform infrared spectroscopy. Measurements included the amount adsorbed, a parameter proportional to fraction of surface-bound repeating units, and the extent of water-induced desorption. Results indicate that the cationic nature of the adsorbing surface is the main driving force for the intense and largely irreversible adsorption of the anionic polyelectrolyte. Ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…These sections that are not in direct contact with the FHA surface are held in place by more strongly bound sections, and can then be reprotonated when the sample is washed. In the case of E5, short chains without a strong bond to the surface are more likely to be washed away [72] so that only strongly bound COO À groups remain.…”
Section: Fha-paa Bondingmentioning
confidence: 99%
“…These sections that are not in direct contact with the FHA surface are held in place by more strongly bound sections, and can then be reprotonated when the sample is washed. In the case of E5, short chains without a strong bond to the surface are more likely to be washed away [72] so that only strongly bound COO À groups remain.…”
Section: Fha-paa Bondingmentioning
confidence: 99%
“…It is well known that drink ingredients, such as the milk component χ -Casein, can adhere to enamel surfaces, altering the structure of the pellicle layer (11). Being an anionic polymer, xanthan gum may adhere to hydroxyapatite as has been shown for another anionic polymer (polyacrylic acid) (27). The bonding between an anionic polymer and the hydroxyapatite surface occurs over very stable ionic bonds through calcium ions (13).…”
Section: Discussionmentioning
confidence: 99%
“…10) the amount of PMAPTAC desorbed appears to be decreased and the surface becomes less negative. One possible explanation is that adsorption (or the formation of the surface complex) at high polymer concentration may involve collective drag motion of anionic polymer molecules toward the adsorbant surface due to chain entanglements, as was demonstrated by Belton et al for the system PAA-tribasic calcium phosphate [24]. It was also shown that the adsorption from concentrated polymer solutions led to a substantial decrease of the fraction of surfacebound repeating units (trails).…”
Section: D) Formation Of Complexes Between the Adsorbed Cationic Polymentioning
confidence: 94%
“…The screening of electrostatic repulsions between the polyion segments leads to contraction of the polymer chains in solution. Consequently, more macromolecules can occupy the available sites for adsorption and an increase in F values has been observed [24]. In contrast to this, an increase in salt concentration should reduce adsorption when electrostatic interactions between the surface and the polymer are the main driving force of this process.…”
Section: C) Adsorption Of Cationic Polyrnersmentioning
confidence: 99%